al-Nashat al-Libi fi al-Bahr al-Mutawassit fi'ahd al-usrah al-Qarmanliyah, 1711 M-1835 M wa atharuhu'ala'alaqatiha bi al-duwal al-ajnabiyah - Abu'Ujaylah, Muhammad al-Hadi'Abd Allah (Banghazi : Jamiʻat Qaryunis, 1997)
Military navigation activity of Libya in the Mediterranean; relations with Europe and U.S.A.; 1835; Ottoman Empire.
Keywords: Libya -- History, Naval; Libya -- History -- 1551-1912.; Libya -- Foreign relations